2022
DOI: 10.1001/jama.2022.15078
|View full text |Cite
|
Sign up to set email alerts
|

Association of HIV Infection With Cardiovascular Pathology Based on Advanced Cardiovascular Imaging

Abstract: IMPORTANCE HIV-associated cardiovascular disease is increasing in prevalence, but its mechanisms remain poorly understood.OBJECTIVE To systematically review data from advanced cardiovascular imaging studies evaluating computed tomographic coronary angiography, positron emission tomography (PET), and cardiac magnetic resonance (MR), in people living with HIV compared with uninfected individuals.DATA SOURCES Three databases and Google Scholar were searched for studies assessing cardiovascular pathology using com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…Importantly, 18F-FDG-PET studies to date have been restricted to predominantly male participants in their fifth decade in nonendemic regions usually with known cardiovascular risk factors. 9 In contrast, the majority of PLWH in SSA are women, typically younger, and with a lower cardiovascular risk profile. 28,53,134,135 There exists Evidence From Anatomic Imaging Computed tomography coronary angiography (CTCA) has been used to further describe the extent and severity of coronary artery disease in HIV.…”
Section: Molecular Imagingmentioning
confidence: 99%
“…Importantly, 18F-FDG-PET studies to date have been restricted to predominantly male participants in their fifth decade in nonendemic regions usually with known cardiovascular risk factors. 9 In contrast, the majority of PLWH in SSA are women, typically younger, and with a lower cardiovascular risk profile. 28,53,134,135 There exists Evidence From Anatomic Imaging Computed tomography coronary angiography (CTCA) has been used to further describe the extent and severity of coronary artery disease in HIV.…”
Section: Molecular Imagingmentioning
confidence: 99%
“…Increased MACE in PWH is thought to be related, in part, to traditional mechanisms as well as to residual inflammation and immune activation . Premature CAD in PWH is characterized by increased noncalcified coronary plaque, which may contribute to increased cardiovascular events . As PWH are increasingly likely to die of non–HIV-related causes, including cardiovascular disease (CVD), it is important to develop a strategy to improve CAD and cardiovascular outcomes in PWH.…”
Section: Introductionmentioning
confidence: 99%
“…Child death from HIV-associated cardiomyopathy has decreased; however, recent studies have shown both transient and chronic functional and structural changes by echocardiography (7,8). Cardiovascular magnetic resonance image (CMR) has emerged as a premier modality for assessment of CVD in PLWH, as it can detect abnormal structural, functional, and tissue characterization parameters better than other imaging modalities (4,5,9). CMR has demonstrated brosis in assessment of late gadolinium enhancement (LGE) and mapping techniques in PLWH ( 4).…”
Section: Introductionmentioning
confidence: 99%